Gender, ethnic, and socioeconomic differences in access to catheter ablation therapy in patients with atrial fibrillation - Hamade, Hani; Jabri, Ahmad; Mishra, Pooja; Butt, Muhammad Umer; Sallam, Sherin; Karim, Saima (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Female patients, patients from racial minorities, and patient with low socioeconomic status have been noted to have less access to catheter ablation for atrial fibrillation. Methods: This is a cross-sectional, retrospective study using a large population database (Explorys) to evaluate the gender, racial and socioeconomic differences in access of catheter ablation therapy in patient with atrial fibrillation. Results: A total of 2.2 million patients were identified as having atrial fibrillation and 6,2760 underwent ablation. Females had ablation in 2.1% of cases while males received ablation in 3.4% of cases. Caucasians had ablation in 3.3% of cases, African Americans in 1.5% of cases and other minorities in 1.2% of cases. Individuals on medicaid underwent ablation in 1.6% of cases, individuals on medicare and private insurance had higher rates (2.8% and 2.9% respectively). Logistic regression showed that female patients (OR 0.608, CI 0.597-0.618, p<0.0001), patients who are African American (OR 0.483, CI 0.465-0.502, p<0.0001) or from other racial minorities (OR 0.343, CI 0.332-0.355, p<0.0001) were less likely to undergo ablation. Patient with medicare (OR 1.444, CI 1.37-1.522, p<0.0001) and private insurance (OR 1.572, CI 1.491-1.658, p<0.0001) were more likely to undergo ablation. Conclusion: Female gender, racial minorities, low socioeconomic status are all associated with lower rates of catheter ablation in management of atrial fibrillation.